Upper Limb Salvage of a Mangled Limb with Reconstruction of Brachial, Ulnar and Radial Arteries Using an Extremely Long Reversed Bifurcated Great Saphenous Vein: A Case Report with Long-Term Follow-Up - Liu, Jun (Int J Gen Med, 2020)
Acute elbow dislocation complicated by arterial injury of upper limb is rare but serious injury. We present the case about destructive injury of brachial, ulnar, and radial arteries with an open posterior dislocation of the right elbow, and a 25cm long reversed bifurcated great saphenous vein graft was applied for arterial reconstruction. The patient had obvious distal pulses after the operation. Ten years’ follow-up showed the good function of the right arm. Using an extremely long vein graft for the upper limb arterial reconstruction is challenging but feasible and provides good results.